Surgical management of delivery with placenta accreta spectrum from the perspective of perinatal obstetrics - A. Yu. Ralnikova; V. F. Bezhenar; B. V. Arakelyan; K. A. Gabelova; V. A. Linde; O. L. Molchanov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. This article raises the issue of planning the timing and method of operative delivery in pregnant women with placenta accreta spectrum. Placenta accreta spectrum is one of the most formidable complications of pregnancy, the delivery of pregnant women with this pathology is accompanied by massive blood loss, and programmed late premature birth leads to an increase in perinatal morbidity.The objective was to evaluate the possibility of prolonging pregnancy to full term in patients with pathology of placenta accreta spectrum.Methods and materials. 94 histories of pregnant women with placenta accreta spectrum, delivered from 2017 to 2023, were analyzed. All patients were divided into 4 groups according to the topography of placenta accreta. According to the assessment of perinatal outcomes, pregnant women were divided into 2 groups: group 1 – pregnant women who delivered at 34–36 weeks of pregnancy (n=82; 87 %); group 2 – patients operated on from 37 to 39 weeks of gestation (n=12; 13 %). The statistical analysis was performed using the program StatTech v. 4.2.7.Results. Among pregnant women whose delivery ended with hysterectomy (n=32, 100 %), the largest proportion of patients had placenta accreta in the area of the parametrium and cervix (n=12, 43.75 %). The average score of newborns in group 1 was 7 points on the Apgar scale at 1 minute after extraction and 8 points on the Apgar scale at 5 minutes; in group2, the average score on the Apgar scale was 8 and 8 points at 1 and 5 minutes.Conclusion. If placenta accreta is suspected and involves the cervix, parametrium, and lower part of the posterior wall of the bladder, a hysterectomy is most likely to be performed. For such pregnant women, it is possible to shift the timing of surgical intervention to 37/38 weeks of gestation in order to improve neonatal outcomes.